1996
DOI: 10.1074/jbc.271.8.4431
|View full text |Cite
|
Sign up to set email alerts
|

Full-length Sequence, Localization, and Chromosomal Mapping of Ameloblastin

Abstract: We report the full-length sequencing, cell type-specific expression, and immunolocalization of a novel gene expressed in rat incisors, which we have designated ameloblastin. Northern blot analysis of RNA from multiple rat and mouse tissues demonstrated high levels of expression of two distinct transcripts of approximately 2.0 and 1.6 kilobase pairs that were expressed only in teeth. In situ hybridization using a digoxigenin-labeled RNA probe showed that the tissue distribution of ameloblastin was limited to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(227 citation statements)
references
References 27 publications
5
221
1
Order By: Relevance
“…35 Ameloblastin was cloned from an enamel protein in rat incisor tooth germs. 4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath.…”
Section: Discussionmentioning
confidence: 99%
“…35 Ameloblastin was cloned from an enamel protein in rat incisor tooth germs. 4,7,18 Sheathlin, considered to be part of the same protein as ameloblastin, was recently cloned from porcine tooth germs. 16 An immunohistochemical study using antibodies that recognize different regions of that protein showed that sheathlin is synthesized by ameloblasts and secreted into the immature enamel matrix with posttranslational and postsecretory modifications and that cleaved NH 2 -terminal polypeptides concentrate in the prism sheath.…”
Section: Discussionmentioning
confidence: 99%
“…During the secretory stage, ameloblasts secrete mostly amelogenin, enamelin and ameloblastin (Hu et al, 1997a;Hu et al, 1997b;Krebsbach et al, 1996;Snead et al, 1985). These proteins catalyze the extension of ribbon-like enamel crystallites comprised of the mineral calcium hydroxyapatite.…”
Section: Dental Enamel Formationmentioning
confidence: 99%
“…The major secretory stage enamel proteins are amelogenin (21,22), ameloblastin (23)(24)(25), and enamelin (26,27). These proteins function specifically during enamel formation, and the disease phenotypes exhibited by mice lacking these genes are confined to the developing teeth and include enamel agenesis (28 -30).…”
mentioning
confidence: 99%